2019
DOI: 10.15694/mep.2019.000013.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between evaluation of the teaching environment using DREEM scores and students’ school learning scores

Abstract: The results from a comprehensive survey of students' perceptions of their educational environment using the Dundee Ready Educational Environment Measure (DREEM) in our Medical School were compared with students' school learning scores. The subjects (n=495) were medical students beyond their first year of medical school. The students were asked to read each DREEM statement carefully and respond using a 5-point Likert-type scale, with responses ranging from strongly agree to strongly disagree. The mean total DRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Scores for all five subscales indicated that both medical and dental students had good perceptions. The higher scores reflect that the undergraduate program has more positive aspects [9]. Four questions earned the lowest score compared to the other questions, showing that the learning environment had some issues.…”
Section: Discussionmentioning
confidence: 95%
“…Scores for all five subscales indicated that both medical and dental students had good perceptions. The higher scores reflect that the undergraduate program has more positive aspects [9]. Four questions earned the lowest score compared to the other questions, showing that the learning environment had some issues.…”
Section: Discussionmentioning
confidence: 95%